2017
DOI: 10.1002/humu.23206
|View full text |Cite
|
Sign up to set email alerts
|

EDNRBmutations cause Waardenburg syndrome type II in the heterozygous state

Abstract: Waardenburg syndrome (WS) is a genetic disorder characterized by sensorineural hearing loss and pigmentation anomalies. The clinical definition of four WS types is based on additional features due to defects in structures mostly arising from the neural crest, with type I and type II being the most frequent. While type I is tightly associated to PAX3 mutations, WS type II (WS2) remains partly enigmatic with mutations in known genes (MITF, SOX10) accounting for only 30% of the cases. We performed exome sequencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 40 publications
0
30
0
3
Order By: Relevance
“…MIR659, EIF3L, MICALL1, C22orf23, POLR2F, SOX10 and RNU6-900P). 15 Homozygous variants in EDNRB have been reported with WS1. 16 Heterozygous variants in EDNRB have been described in individuals with WS without HD and also with isolated HD.…”
Section: Resultsmentioning
confidence: 99%
“…MIR659, EIF3L, MICALL1, C22orf23, POLR2F, SOX10 and RNU6-900P). 15 Homozygous variants in EDNRB have been reported with WS1. 16 Heterozygous variants in EDNRB have been described in individuals with WS without HD and also with isolated HD.…”
Section: Resultsmentioning
confidence: 99%
“…The Endothelin receptor A is present in vascular smooth muscle cells and mediates vasoconstriction and proliferation (Gordon et al, ). On the other hand, the Endothelin receptor B is found in the brain, endothelium, and smooth muscle cells and mediates endothelium‐dependent vasodilation through the release of nitric oxide, prostacyclin, and adrenomedullin (a circulating vasodilatory and natriuretic peptide of vascular endothelial and smooth muscle cell origin) (Issa et al, ; Kawasaki‐Nishihara, Nishihara, Nakamura, & Yamamoto, ). Regarding the role of the Endothelin Receptors in development, it has been shown that the Edn1/Ednra cell signaling plays a critical role in the specification, migration and patterning of mandibular identity in post‐migratory NCCs in different animal models such as Xenopus , zebrafish, chick, rat, rabbit and mouse (Bonano et al, ; Clouthier et al, ; Gordon et al, ; Kempf, Linares, Corvol, & Gasc, ; Miller, Schilling, Lee, Parker, & Kimmel, ; Sabrautzki et al, ; Spence, Anderson, Cukierski, & Patrick, ; Treinen, Louden, Dennis, & Wier, ).…”
Section: Chemical Agentsmentioning
confidence: 99%
“…Additionally, overstimulation of beta‐catenin signals in NCCs at the time of their migration, using LiCl treatment, induced nuclear translocation of beta‐catenin and Lef‐1 up‐regulation in these cells and provoked a marked inhibition of cell delamination and migration (de Melker, Desban, & Duband, ). Lithium has also been show to play a role in the onset of auditory‐pigmentary syndromes and in NCPs (Waardenburg Syndrome Type 2 and Tietz Syndrome), which are characterized by sensorineural hearing loss and abnormal pigmentation of the hair and skin (Issa et al, ; Jin & Thibaudeau, ; Leger et al, ; Yasumoto et al, ). Also, in an animal study performed with mouse, in utero treatment with LiCl rescued mandibular molar tooth morphogenesis in mouse embryos lacking activin‐βA (Inhba −/− ) (Jia et al, ; Shan et al, ).…”
Section: Chemical Agentsmentioning
confidence: 99%
“…Mutations in several genes implicated in neural crest cell function are responsible for various human developmental defects, such as Waardenburg syndrome, characterized by sensorineural hearing loss and pigmentation anomalies in hair, skin and irises ( Baxter et al, 2004 ; Etchevers et al, 2006 ). Waardenburg syndrome accounts for about 3% of congenital deafness worldwide ( Issa et al, 2017 ). Significantly, many of the genetic mutations associated with human neurocristopathies also occur in rodents, manifesting themselves in the form of reduced and/or altered pigmentation phenotypes.…”
Section: Introductionmentioning
confidence: 99%